Platinum(ii) complexes with rutaecarpine and tryptanthrin derivatives induce apoptosis by inhibiting telomerase activity and disrupting mitochondrial function. Issue 10 (30th August 2018) - Qin, Qi-Pin; Zou, Bi-Qun; Hu, Fei-Long; Huang, Guo-Bao; Wang, Shu-Long; Gu, Yun-Qiong; Tan, Ming-Xiong
Abstract : BrTry-Pt is a telomerase inhibitor targeting the c-myc promoter, and triggered T-24 cell apoptosis, which also caused mitochondrial dysfunction and S phase arrest. Abstract : Four new platinum(ii ) complexes, [Pt(Rut)(DMSO)Cl2 ] (Rut-Pt ), [Pt(Try)(DMSO)Cl2 ] (Try-Pt ), [Pt(ITry)(DMSO)Cl2 ] (ITry-Pt ) and [Pt(BrTry)(DMSO)Cl2 ] (BrTry-Pt ), with rutaecarpine (Rut), tryptanthrin (Try), 8-iodine-tryptanthrin (ITry) and 8-bromo-tryptanthrin (BrTry) as ligands were synthesized and fully characterized. In these complexes, the platinum(ii ) adopts a four-coordinated square planar geometry. The inhibitory activity evaluated by the MTT assay showed thatBrTry-Pt (IC50 = of 0.21 ± 0.25 μM) could inhibit the growth of T-24 tumor cells (human bladder cancer cell line) more so than the other three complexes. In addition, all of these Pt complexes exhibited low toxicity against non-cancerous HL-7702 cells.BrTry-Pt induced cell cycle arrest in the S phase, leading to the down-regulation of cyclin A and CDK2 proteins.BrTry-Pt acts as a telomerase inhibitor targeting the c-myc promoter. In addition, BrTry-Pt also caused mitochondrial dysfunction. Importantly, the in vitro anticancer activity ofBrTry-Pt was higher than those ofRut-Pt, Try-Pt andITry-Pt, and it was more selective for T-24 cells than for non-cancerous HL-7702 cells.